A holistic and sustainable approach for recovery of phosphorus via struvite crystallization from synthetic distillery wastewater. (1st May 2020) - Kumari, Soni; Jose, Sanoj; Tyagi, Megha; Jagadevan, Sheeja
Abstract: Phosphorus is a limited resource and at the current usage, world's reserves of phosphate rocks will soon get exhausted. The present study focuses on phosphorus recovery in the form of struvite from synthetic distillery wastewater. A response surface methodology was adopted to optimize process parameters (pH, concentration of phosphorus, ammoniacal nitrogen and magnesium) for struvite precipitation and removal of phosphate from wastewater. The optimized values for pH, molar ratio of NH 4 + : PO 4 − 3 and Mg 2 + : PO 4 − 3 were found to be 9.0, 2.28 and 1.72 respectively, resulting in 95% phosphate removal and 3306 mg/L yield of struvite. This study also investigated the effect of phenol and melanoidins on phosphate removal efficiency, purity and yield of the struvite. When concentration of phenol was increased from 0 to 9000 mg/L in a melanoidins free solution, the phosphate percentage removal decreased from 99% to 93% and the struvite crystal purity decreased from 96% to 62%. However, melanoidins containing wastewater showed 99%–88%, 93%–41% and 3700 mg/L to 2900 mg/L decrease in phosphate percentage removal, struvite purity and yield of precipitate respectively. Furthermore, dilution of distillery wastewater with seawater (source of magnesium) at 1:1.3 M ratio of P:Mg, serves as an economical and sustainable route for struvite crystallization. The pot trial experiments conducted with Brassica alba demonstrated promising fertilizer potential of the recovered struvite, comparable with commercially available fertilizers. The present study demonstrates that struvite crystallization from distillery wastewater is a sustainable and promising technology which could be applied efficiently for remediation of nutrient-rich wastewater and the recovered struvite can be employed as an alternate source of slow-release fertilizer for plants. Graphical abstract: Image 1 Highlights: Phosphorus was recovered as struvite from synthetic distillery wastewater. Optimization of process parameters through Central Composite Design. Phenol and melanoidins affects phosphate removal, purity and yield of crystals. Seawater demonstrated to be an efficient alternative to magnesium chloride. The recovered struvite proved to be good fertilizer for the tested plants.